Aplikasi Model Lima Kekuatan Porter pada Restoran Drupadi - Sevenpri Candra (Binus Business Review, 2013)
Internet is one of the global information dissemination media. It provides an easy way of doing business and facilitating users to communicate and obtain information needed quickly and accurately with the use of the website. To view the competition within the industry, the author uses Porter Five Forces Analysis method. ByPorter analysis, it showed the bargaining power of consumers in strong position. Consumer satisfaction can be achieved by providing quality products and good services. So that, the Internet service, which is a global market with 24-hour nonstop access, can be used as a media campaign and can provide information to customers.